Answer:
v = <-3√2 , 3√2>
v = <-10 , 0>
Explanation:
∵ Vector v in the same direction of vector u
∴ u = v/║v║
∵ u = <-3 , 3> ⇒ convert it to unit vector
∴ ║u║ = √(-3)² + (3)² = √18 = 3√2
∵ Unit vector = u/║u║
∴ u = <-3 , 3>/3√2 =<-3/3√2 , 3/3√2>
∴ u = <-1/√2 , 1/√2>
∵ u = v/║v║
∴ u ║v║ = v
∵ ║v║ = 6
∴ v = 6 <-1/√2 , 1/√2>
∴ v = <-6/√2 , 6/√2> ⇒ multiply up and down by √2
∴ v = <-3√2 , 3√2>
∵ Vector v in the same direction of vector u
∴ u = v/║v║
∵ u = <-10 , 0> ⇒ convert it to unit vector
∴ ║u║ = √(-10)² + (0)² = √100 = 10
∵ Unit vector = u/║u║
∴ u = <-10 , 0>/10 =<-1 , 0>
∴ u = <-1 , 0>
∵ u = v/║v║
∴ u ║v║ = v
∵ ║v║ = 10
∴ v = 10 <-1 , 0>
∴ v = <-10 , 0>
∴ v = <-10 , 0>